ANALISIS PENGARUH RASIO KENDARAAN BELOK KANAN TERHADAP KINERJA SIMPANG TAK BERSINYAL - Christinna Odilla Saba; Don Gaspar Noesaku da Costa; Engelbertha N.B. Seran (Eternitas: Jurnal Teknik Sipil, 2022)
The ratio of right-turning vehicles is very influential on delays and queuing opportunities at unsignalized intersections. This study will compare the effect of the right turn ratio on the performance of the intersection at two locations with different right turn ratio characteristics, namely at the Timor Raya - Nangka street intersection which has a high right turn volume and the Samratulangi Raya - Samratulangi I street intersection with a low right turn volume. The standard of intersection performance is according to the 1997 MKJI guidelines. At the intersection of Timor Raya - Nangka street, the results show that the ratio of right-turning vehicles affects the performance of unsignaled intersections, with a degree of saturation (DS) = 1.246 > 0.75, delay (D) = 57 ,80 sec/smp > 25 sec/smp and queue probability (QP)= 63,6 %-130,4 % > 50 %. The effect of the right turn ratio on the degree of saturation (DS) = 97.53%, delay (D) = 72.12% and queue probability (QP) = 96.15%-95.37% with level of service F (very bad). On Samratulangi Raya - Samratulangi I street intersiction, the results show that the right turn ratio has no effect on the performance of unsignalized intersections, with a degree of saturation (DS) = 0.586 < 0.75, delay (D) = 9.85 sec/smp < 25 sec/smp and queue probability (QP)= 14,5 %-30,9 % < 50 % with level of service B (good). The solution at the Timor Raya - Nangka road intersection is to eliminate side barriers, widen the road, install right-turning signs and regulate one-way traffic.